Aspects of Stage-by-Stage Diagnosis of Pulmonary Mycobacteriosis in Real Clinical Practice - N. L. Karpina; A. D. Egorova; Ya. O. Chesalina; I. Yu. Shabalina; A. E. Ergeshov (Туберкулез и болезни лёгких)
The objective: to analyze the effectiveness of etiological verification of pulmonary mycobacteriosis when using various biological materials at different diagnostic stages.Subjects and Methods. In Center for Diagnosis and Rehabilitation of Respiratory Diseases, CTRI, the results of stage-by-stage examinations of 142 patients (from 2018 to 2022) were analyzed. A retrospective, prospective, cohort, open study was conducted. Inclusion criteria: pulmonary mycobacteriosis etiologically verified by comprehensive microbiological examinations (molecular genetic and cultural tests) (with retrospective analysis after all stages of examination). Exclusion criteria: HIV infection. 115 women and 27 men were enrolled in the study, the age ranged from 21 to 86 years, the mean age was 57,9 years.All patients referred to CTRI for examination due to newly detected changes in the lungs (bronchiectasis, focal changes, and cavities). For etiological verification of the diagnosis, microbiological sputum testing was performed (Stage 1 of the examination); when negative results were obtained, bronchoscopy was prescribed and bronchobiopsies were used for microbiological and molecular genetic diagnostics – Stage 2. In case of negative results of Stage 2, the patient was recommended to undergo a diagnostic resection of the lung – Stage 3 of the examination. At all stages, specimens were sent for comprehensive microbiological testing: fluorescent microscopy to detect acid-fact mycobacteria, real-time polymerase chain reaction (PCR-RV) to detect NTBM DNA. Identification of NTBMB was carried out by molecular genetic methods (PCR for the presence of MTB DNA/NTBM (SYNTOL, Russia), and on DNA strips (GenoType Mycobacterium CM\AS Hain Livescience, Germany)). Specimens were cultured on a liquid medium in the ВАСТЕС MGIT960 (BD, USA).The diagnosis of mycobacteriosis was established in accordance with the diagnostic criteria proposed in the guidelines of the American Thoracic Society (ATS) and the Infectious Diseases Society of America (IDSA) (2020): detection of NTBM in 2 sputum samples or in 1 sample of bronchobiopsy specimens or in 1 surgical specimens [15].The studied data were entered to the Microsoft Office Excel sheet (Microsoft, USA) for statistical processing; the level of statistical significance of differences was taken as 0.05.Results. It was found that slow-growing NTBM were identified as etiologically significant in 93.0%, of which 78.1% was M. avium, fast-growing NTBM were represented only by M. abscessus, 7% of observations. During X-ray examination, the bronchiectatic form – 52.1% (74/142) was detected more often compared to the abdominal – 30.9% (44/142) and focal forms – 16.9% (24/142) (p<0.001). When verifying mycobacteriosis in patients with a negative sputum test – Stage 2 of the examination – the effectiveness was 91.0% (80/88). Regardless of the radiological form of the disease and dissemination of the disease, bronchoscopy revealed pathology of the tracheobronchial tree in 85.2% of cases, mainly in the form of bronchitis with purulent secretions.